The Effect of Implementing SI PETIR (An Innovative Boiler Lance Tube Straightening Solution) on Sootblower Maintenance Efficiency at the 660 MW Adipala Coal-Fired Power Plant in Central Java - Dea Amanda Kahendrastuti; Prihatno Kusdiyarto (Program Studi Sarjana Terapan Teknik Mesin, Fakultas Vokasi, Universitas Negeri Yogyakarta, 2026)
This study aims to analyze the impact of the implementation of the SI PETIR system on the efficiency of sootblower maintenance at the 660 MW Adipala Coal-Fired Power Plant in Central Java through improvements in time efficiency, reductions in maintenance costs, and enhancements in operational reliability. The methodology employed is a descriptive-comparative approach using a case study design. Data were obtained through field observations, documentation, and interviews with maintenance technicians, then analyzed by comparing conditions before and after the implementation of the SI PETIR system based on MTTR, maintenance costs, and operational reliability indicators. The research results show that SI PETIR was able to reduce MTTR from 7,200 minutes to 720 minutes, cut maintenance costs from Rp 95,070,000.00 to Rp 9,970,000.00, and improve operational reliability from 83.33% to 96.67%, thereby proving to be effective and economical in improving sootblower maintenance performance.